Comparative radiological assessment of orbital volume restoration following management of zygomatic complex fractures. Issue 5 (September 2020) - Shadamarshan R, Arunkumar; Roy Chowdhury, Sanjay Kumar; Krishnaprabhu, Rajkumar
Abstract: Objective: Comparative radiological assessment of Orbital volume (OV) restoration following management using an established protocol in Low (LE) (Group I), Middle (ME) (Group II) and High Energy (HE) (Group III) Zygomatic Complex (ZMC) fractures on Non-Contrast Computed Tomography (NCCT). Methods: A prospective study was conducted with a total of 60 patients (20 in each group) which included patients greater than 18 years with clinical and radiological diagnosis ZMC fractures. Patients with history of Midface fractures and/or surgical procedures, pre-existing facial asymmetry were excluded. The volume of the bony orbit on the affected side (OVpre ) and the unaffected side(OVN ) were elicited using the software available with the CT scanner. Management was undertaken according to contemporary protocols. Post-surgical orbital volume (OVpost ) on the treated side was elicited after 06 months. Results: No significant differences between OVN and OVpre, OVpre and OVpost, OVN and OVpost were evident in both Group I and Group II. In Group III, significant differences between OVN and OVpre as well as between OVpre and OVpost were identified. No significant differences were evident between OVN and OVpost . Conclusion: This study validates this widely used protocol based on restoration of orbital volume. It can be concluded that management of LE and ME fractures have to be driven clinically other than OV, while with HE fractures, OV is an important objective parameter that should be addressed. The contemporary protocols used in the current study restores the volume of the affected orbit.